PENGARUH MOTIVASI DAN PEMANFAATAN PERPUSTAKAAN MELALUI SIKAP TERHADAP HASIL BELAJAR IPS TERPADU - Sukmawati Sukmawati; Yon Rizal; Tedi Rusman (JEE (Jurnal Edukasi Ekobis), 2014)
Learning outcomes in Integrated Social Science is low. The aim of this research is to know influence of learning motivation and library utilization through attitude toward learning outcomes of Integrated Social Sciences. Method of research uses descriptive verification. Analysis data uses path analysis. The result of research showed:(1)There is influence of learning motivation toward attitude; (2)There is influence of library utilization toward attitude; (3)There is direct influence of learning motivation toward learning outcomes in Integrated Social Science; (4)There is correlation of learning motivation and library utilization; (5)There is direct influence of library utilization toward learning outcomes in Integrated Social Science; (6)There is influence attitude toward learning outcomes in Integrated Social Science; (7)There is influence of learning motivation through the attitude toward learning outcomes in Integrated Social Science; (8)There is influence of library utilization through attitude toward learning outcomes in Integrated Social Science; (9)There is influence of learning motivation and library utilization toward attitude; (10)There is influence of learning motivation, library utilization and the attitude toward learning outcomes in Integrated Social Science. Hasil belajar IPS Terpadu rendah. Penelitian ini bertujuan untuk mengetahui pengaruh motivasi dan pemanfaatan perpustakaan melalui sikap terhadap hasil belajar IPS Terpadu. Metode penelitian deskriptif verifikatif. Analisis data menggunakan analisis jalur. Hasil analisis menunjukan: (1)Ada pengaruh motivasi belajar terhadap sikap; (2)Ada pengaruh pemanfaatan perpustakaan terhadap sikap; (3)Ada pengaruh motivasi belajar terhadap hasil belajar IPS Terpadu; (4)Ada hubungan motivasi belajar dan pemanfaatan perpustakaan; (5)Ada pengaruh pemanfaatan perpustakaan terhadap hasil belajar IPS Terpadu; (6)Ada pengaruh sikap terhadap hasil belajar IPS Terpadu; (7)Ada pengaruh motivasi belajar melalui sikap terhadap hasil belajar IPS Terpadu; (8)Ada pengaruh pemanfaatan perpustakaan melalui sikap terhadap hasil belajar IPS Terpadu; (9)Ada pengaruh motivasi belajar dan pemanfaatan perpustakaan terhadap sikap;(10)Ada pengaruh motivasi belajar, pemanfaatan perpustakaan dan sikap terhadap hasil belajar IPS Terpadu. Kata kunci: hasil belajar,motivasi,pemanfaatan perpustakaan,sikap